(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Biosurfactants are surface-active biomolecules produced by microorganisms that have different applications in solving many environmental problems. This study was carried out to screen biosurfactant-producing bacteria isolated from hydrocarbon-contaminated soil of Kano Metropolis, Kano State- Nigeria. Soil samples were collected and processed. Biosurfactant-producing bacteria were enumerated, isolated and characterized using cultural, morphological and biochemical characteristics. Blood haemolysis, oil drop collapse and oil displacement tests were employed for the screening of the bacterial isolates for the potential to produce biosurfactant. The viable aerobic heterotrophic bacterial count of the samples ranges from 1.0 to 8.4×106 cfu/g. Eight bacterial genera were biochemically identified as Pseudomonas aeruginosa, Enterobacter cloacae, Pantoea agglomerans, Pseudomonas sp., Bacillus subtilis, Enterobacter alvei, Bacillus sp. and Klebsiella sp. Bacillus subtilis had the highest frequency of occurrence of 5(27%) while Bacillus sp. and Enterobacter alvei have the least occurrences of 1(6%) each. The eight identified bacterial isolates were all positive for the haemolysis test, drop collapse and oil displacement test.